A profile of male meiosis, chromosomal variation and status in species of Impatiens from North-West Himalaya in India. Issue 3 (3rd July 2017) - Singhal, Vijay Kumar; Kumar, Rohit; Singhal, Himshikha; Kumar, Puneet; Kaur, Dalvir; Kaur, Maninder; Rana, Pawan Kumar; Gupta, Raghbir Chand
Abstract: Impatiens (Balsaminaceae), a genus of over 1000 species, is represented by 209 species in India, particularly in South India and Himalayas. In spite of attempts made by several Indian cytologists, the chromosome counts are available for only 95 species, through karyological studies, or pollen mitosis or meiotic preparations. The investigated species revealed a considerable amount of dysploid chromosomal variation. We have studied male meiosis in 53 accessions from 14 species collected from unexplored regions of North-West Himalaya in India. Chromosome numbers were confirmed for nine species and numbers different from earlier records were found in five species. Four species were documented for chromosome counts for the first time. Out of the 14 species covered presently, nine species possessed dysploid cytotypes with different diploid chromosome counts. Five species possessed more than one diploid chromosome counts. Dysploidy seems to be quite favourable for causing chromosomal variation in the genus. Based on compiled chromosomal data, it is apparent that there is a lot of variation in base numbers. Among the different basic numbers prevalent in the genus, we are of the opinion that x =  7, x =  8, x =  9 and x =  10 seem to be the most common. In addition, a list of North-West Himalayan species of the genus which are yet to be worked out chromosomally and those depicting chromosomal variation has also been included.